2008
DOI: 10.1111/j.1744-7909.2008.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Genes in Arabidopsis Development

Abstract: Histone acetylation and deacetylation are directly connected with transcriptional activation and silencing in eukaryotes. Gene families for enzymes that accomplish these histone modifications show surprising complexity in domain organization, tissue-specific expression, and function. This review is focused on the family of histone deacetylases (HDACs) that remove the acetyl group from core histone tails, resulting in a "closed" chromatin and transcriptional repression. In Arabidopsis, 18 HDAC genes are divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
257
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(263 citation statements)
references
References 64 publications
6
257
0
Order By: Relevance
“…Lys acetylation can have a strong impact on the biochemical function of proteins as the transfer of the acetyl group to Lys masks the positive charge, which is known to be important in many catalytic centers of enzymes, as well as for protein-protein and protein-DNA interactions. In plants, Lys acetylation was, until recently, mainly thought to occur on histone proteins as regulatory mechanism for transcription and chromatin functions (Hollender and Liu, 2008). However, several central metabolic enzymes of diverse subcellular compartments were recently discovered to be Lys acetylated in Arabidopsis (Arabidopsis thaliana), and in vitro deacetylation tests confirmed that Lys acetylation affects enzyme activities and protein functions (Finkemeier et al, 2011;Wu et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lys acetylation can have a strong impact on the biochemical function of proteins as the transfer of the acetyl group to Lys masks the positive charge, which is known to be important in many catalytic centers of enzymes, as well as for protein-protein and protein-DNA interactions. In plants, Lys acetylation was, until recently, mainly thought to occur on histone proteins as regulatory mechanism for transcription and chromatin functions (Hollender and Liu, 2008). However, several central metabolic enzymes of diverse subcellular compartments were recently discovered to be Lys acetylated in Arabidopsis (Arabidopsis thaliana), and in vitro deacetylation tests confirmed that Lys acetylation affects enzyme activities and protein functions (Finkemeier et al, 2011;Wu et al, 2011).…”
mentioning
confidence: 99%
“…Generally, protein acetyltransferases and deacetylases are known to catalyze the reversible modification of the « N-group of Lys. In addition to the classical family of histone deacetylases, a second family of protein deacetylases exists, namely the sirtuins, which are conserved across bacteria, yeast (Saccharomyces cerevisiae), plants, and animals (Hollender and Liu, 2008). Sirtuins catalyze an NAD + -dependent deacetylation of acetyl-Lys in proteins and thereby produce a deacetylated Lys, as well as the metabolites nicotinamide and 29-Oacetyl-ADP-ribose.…”
mentioning
confidence: 99%
“…Arabidopsis histone deacetylases (HDACs) have been classified into three families (Hollender and Liu, 2008;Alinsug et al, 2009). The first one contains members homologous to the yeast RPD3 (reduced potassium deficiency 3) and HDA1 proteins; the second, the HD-tuins (HDT1 through 3), appears to be plant-specific (Wu et al, 2000;Dangl et al, 2001) and the third family contains homologs of the yeast silent information regulator 2 (Sir2), a (NAD)-dependent HDAC (Pandey et al, 2002;Hollender and Liu, 2008). The main conclusion that we can extract from the data available is that a fine balance between HAT and HDAC activities is at the core of crucial processes during plant development.…”
Section: Histone Acetylases and Deacetylasesmentioning
confidence: 99%
“…[14][15][16][17][18] Besides its role in gene expression, plant histone acetylation plays crucial roles in the crosstalk between genomes and the environment during plant responses to diverse stresses at the cellular and organismal levels. [19][20][21][22][23][24] Acetylation occurs at many histone lysine residues and regulates chromatin activity by at least 2 different mechanisms. On the one hand, individual acetylation marks have precise function on a specific chromatin-based process independent of other acetylated residues.…”
Section: Introductionmentioning
confidence: 99%